Pelatihan Bantuan Hidup Dasar Pada Kelompok Sekeha Teruna Sebagai Antsisipasi Cedera Pariwisata di Desa Dawan Kaler Klungkung - I Made Sukarja; I Wayan Sukawana; Ni Made Wedri (Poltekkes Kemenkes Denpasar, 2019)
Basic Life Support Training at Sekeha Teruna Group as a Tourism Injury Prediction in Dawan Kaler Klungkung Village. The development of tourist villages, in general, has taken into account the security and safety of tourists so that tourists feel comfortable enjoying the natural beauty of Bali. Nevertheless, most of the tourist attractions associated with the rice fields and forests are sometimes relatively slippery. In addition, Bali is an area with high rainfall. This situation contains the risk of accidents, which impact the occurrence of casualties either mild or severe even threaten the lives of tourists. This condition makes tourists feel concerned. Tourist accidents warn that people in Bali including Terraces and Teruni as prospective workers in tourism should have basic life support skills and skills. This community service aims to make the sekeha teruna able to do basic life support. The results of this activity indicate that there is an increase in knowledge after being given training with an average score of 46 to 80. And 100% of participants are able to practice basic life support techniques. It is recommended to the puskesmas to continue the training program.Keywords: basic life support